Attitudes Towards The Foreign Products From Animosity, Boycott And Ethnocentrism Perspectives: The Case Of Turkish Students - Barutçu, Süleyman; Saritaş, Emel; Adigüzel, Deniz Ünal (European Scientific Journal, ESJ, 2016)
The purposes of this study are to determine Turkish students’ attitudes towards products imported from countries that Turkey has political and economic crisis, and understand their buying behavior from animosity, boycott and ethnocentrism perspectives. Analyzing these concepts and determining their attitudes towards foreign products will provide useful information about Turkish students markets and help international/global marketing manager to develop their marketing mix, especially for promotion mix strategies. The survey was conducted at Pamukkale University, Denizli- Turkey with 394 students. The relationship between attitudes towards importing foreign products and purchase intention are high, and Turkish student animosity and ethnocentrism are considered to have an influence on the perception of foreign products. Crisis and ethnocentrism are found as the most two important determinants to buy international products imported from countries that Turkey has politic/economic problems. Foreign companies that export their products or manufactured in Turkey should use adaptation strategies in order to decrease Turkish students’ ethnocentrism.